220k views
5 votes
Which will result in a difference of squares?

(-7x+4)(-7x+4)
(-7x+4)(4-7%)
0 (-7x+4)(-78-4)
(-7x+4)(7x-4)

1 Answer

5 votes

Answer:

The expression which will result in difference of two squares is:

(–7x + 4)·(–7x – 4)

Explanation:

We know that the formula of the type:

(a-b)(a+b)=a²-b²

i.e. it is a difference of two square quantities. (a^2 and b^2)

since,

a= -7x , b=4

(-7x+4)(-7x-4)= (-7x)² - (4)²

=(7x)² - 4²

So the expression is a difference of two square quantities:

(7x)² and (4)²

Hence the answer is (–7x + 4)·(–7x – 4)....

User Hallodom
by
6.3k points